Analisis Laju Infiltrasi Tanah Gambut Pada Beberapa Penggunaan Lahan Di Desa Mega Timur Kecamatan Sungai Ambawang Kabupaten Kubu Raya - Amelia, Nindia; Widiarso, Bambang; Romiyanto, Romiyanto (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Mega Timur Village, Kubu Raya Regency has a type of peat soil that is utilized by the community as a livelihood such as farming and gardening. The availability of water in the land will affect plant growth and agricultural yields, one of which is the process in the hydrological cycle that plays a very important role in controlling surface flow and the availability of water in the soil is infiltration. This study aims to identify the physical properties of peat soil and determine the differences in infiltration rates in the use of rubber plantations, oil palm plantations and mixed gardens in Mega Timur Village. The study was conducted for 4 months from September to December in Mega Timur Village, Sungai Ambawang District, Kubu Raya Regency. Sampling was carried out using the transect method with a distance between points of 20 meters at three land uses of five points each. The results of the One Way ANOVA test on land use showed that land use did not significantly affect the parameters of soil maturity, bulk density, total porosity, field condition water content and permeability at a soil depth of 0-30 cm. The constant infiltration rate in mixed gardens was 452.14 mm/hour (very fast criteria), rubber gardens were 338.33 mm/hour (very fast criteria) and oil palm gardens were 195.80 mm/hour (fast criteria).